Legal Aspects of the Implementation of a Pledge of a Bill of Lading as a Security: National Legal Realities - Haliantych, Mykola K.; Kostruba, Anatoliy V.; Maydanyk, Nataliia I. (International Journal of Criminology and Sociology, 2021)
The purpose of this article is a detailed study of the legal aspects of the implementation of the bill of lading in the context of the peculiarities of state legislation. Since the bill of lading is a security that gives the owner the legal authority to receive the goods, it can be accepted as collateral, as it is supported by a specific material value – its market value. At the moment, the problem of the bill of lading in the realities of Ukraine has become particularly relevant, as the world economy is now on the brink of crisis due to external factors, and the market needs additional investment, financing, budget expansion at various structural levels crisis. The methods used in the study are an analysis of the relevant legislation of Ukraine and Germany, as well as a comparative analysis, which leads to a vision of the lack of relevant functionalities in particular legislation. As a result of research, the authors found out whether the national conditions for obtaining a pledge under the bill of lading are favourable and what problems a legal entity may face in the case of this procedure. In conclusion, a number of additions were made that would need to be added to the actual legislation to facilitate the procedure for issuing funds secured by a bill of lading.